2010
DOI: 10.1016/j.neuroimage.2009.12.055
|View full text |Cite
|
Sign up to set email alerts
|

Motor imagery in response to fake feedback measured by functional near-infrared spectroscopy

Abstract: Motor imagery in response to fake feedback measured by functional near-infrared spectroscopy AbstractThe objective of this study was to describe brain oxygenation patterns during motor imagery (MI) in response to feedback using functional near-infrared spectroscopy (fNIRS). fNIRS was recorded over the primary motor cortex in 15 healthy subjects using a right hand motor task during four fake feedback conditions: MI without Feedback (MI(0)), MI with positive (MI(+)) and negative Feedback (MI(-)) and during actu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 72 publications
4
13
0
Order By: Relevance
“…Finally, lower feedback values in the SHAM group may affect the efficacy of the neurofeedback. Although a previous study reported that negative feedback did not reduce the motor imagery-related cortical activation, 22 it is possible that the lower feedback values resulted in reduced cortical reorganization and poorer functional recovery in the SHAM group. In addition, it is also possible that the lack of contingency of the feedback in the SHAM group resulted in less effective neuromodulation.…”
Section: Strokementioning
confidence: 71%
See 1 more Smart Citation
“…Finally, lower feedback values in the SHAM group may affect the efficacy of the neurofeedback. Although a previous study reported that negative feedback did not reduce the motor imagery-related cortical activation, 22 it is possible that the lower feedback values resulted in reduced cortical reorganization and poorer functional recovery in the SHAM group. In addition, it is also possible that the lack of contingency of the feedback in the SHAM group resulted in less effective neuromodulation.…”
Section: Strokementioning
confidence: 71%
“…The near-infrared spectroscopy (NIRS) system, which can measure task-related regional hemodynamic changes in oxygenated hemoglobin (oxyHb) and deoxygenated hemoglobin using infrared light without onerous constraint, 21 may be useful as a neurofeedback tool. Several studies have used NIRS as a neurofeedback or brain-computer interface tool, [22][23][24] and we previously reported that the NIRS-mediated neurofeedback enhances the motor imagery-related PM activation in healthy subjects. 23 Reorganization of the ipsilesional PM has been suggested to be important in recovery of hand function after stroke.…”
Section: April 2013mentioning
confidence: 96%
“…This could be responsible for the small and non-significant correlation between self-assessment scores of kinesthetic motor imagery and average feedback height in this study. A previous study using NIRS showed that positive and negative feedback increases motor imagery-related cortical activation [60], which suggests that it is not greater feedback, but rather appropriate feedback, of motor imagery performance that is most helpful for improved motor imagery. Further studies are needed to determine the most effective feedback method for improving behavioral performance.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies have investigated the potential of a real-time neurofeedback system for neurorehabilitation (Holper and Wolf, 2010; Fazli et al, 2012; Mihara et al, 2013). The real-time visualization of cortical activity may be useful for intraoperative monitoring.…”
Section: Discussionmentioning
confidence: 99%